1997
DOI: 10.2307/3345421
|View full text |Cite
|
Sign up to set email alerts
|

Student Interpretations of Teacher Verbal Praise in Selected Seventh- and Eighth-Grade Choral Classes

Abstract: Choirs who were unfamiliar with the teacher differed from the teachers' own students in interpreting the praise: Students who knew a teacher labeled the praise as deserved in five clips, but unfamiliar choirs thought the praise served an instructional purpose. In four clips, choirs differed in their interpretations of the type of instructional praise.Students familiar with a teacher recognized their teacher's intent in praising in 12 of 16 clips. In some situations, familiarity with a teacher and context made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…She used a relatively high percentage of scaffolding language during those interactions. The need for music teachers to provide individualized attention is reinforced by a recent finding that students in middle school choral ensembles differ in their interpretations of teacher praise (Taylor, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She used a relatively high percentage of scaffolding language during those interactions. The need for music teachers to provide individualized attention is reinforced by a recent finding that students in middle school choral ensembles differ in their interpretations of teacher praise (Taylor, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In each instance, the researchers have indicated a general lack of research concerning the relationship between teacher instructional behaviors and student learning or attitudes. This relationship has received little attention at the middle school level, although researchers have examined several areas of conductor behaviors, including repertoire choice (Funderburk-Galvan, 1988), approval and disapproval comments (Derby, 2001;Walker, 1990;Taylor, 1997;Fiocca, 1989), and the organization of rehearsal time (Copley, 1990).…”
Section: Teacher Instructional Language and Student Experience In Midmentioning
confidence: 99%
“…I identified several studies concerning student perception of teacher behavior (Morgan, 1992;Schmidt, 1995;Stamar, 1995;Taylor, 1995). These studies explored choral students' responses that dealt with perceptions of their teachers.…”
Section: Methodsmentioning
confidence: 99%
“…Positive teacher feedback needs to be perceived by students as being sincere, as students want to feel that they have earned this praise. A recent study by Taylor (1997) confirmed that students are able to distinguish between deserved teacher praise and merely encouraging comments. Salzberg and Salzberg (1981), in their study of the effect of negative and positive feedback in improving left-hand positions of elementary string players, showed that praise after a longer training session resulted in the greatest improvement for all subjects.…”
Section: Introductionmentioning
confidence: 94%